Manipulation of components of the renin angiotensin system in renal proximal tubules fails to alter atherosclerosis in hypercholesterolemic mice - Masayoshi Kukida; Naofumi Amioka; Dien Ye; Hui Chen; Jessica J. Moorleghen; Ching-Ling Liang; Deborah A. Howatt; Yuriko Katsumata; Yuriko Katsumata; Motoko Yanagita; Motoko Yanagita; Hisashi Sawada; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background and objectiveWhole body manipulation of the renin-angiotensin system (RAS) consistently exerts profound effects on experimental atherosclerosis development. A deficit in the literature has been a lack of attention to the effects of sex. Also, based on data with gene-deleted mice, the site of RAS activity that influences lesion formation is at an unknown distant location. Since angiotensin (AngII) concentrations are high in kidney and the major components of the RAS are present in renal proximal tubule cells (PTCs), this study evaluated the role of the RAS in PTCs in atherosclerosis development.Methods and resultsMice with an LDL receptor −/− background were fed Western diet to induce hypercholesterolemia and atherosclerosis. We first demonstrated the role of AT1 receptor antagonism on atherosclerosis in both sexes. Losartan, an AngII type 1 (AT1) receptor blocker, had greater blood pressure-lowering effects in females than males, but equivalent effects between sexes in reducing atherosclerotic lesion size. To determine the roles of renal AT1a receptor and angiotensin-converting enzyme (ACE), either component was deleted in PTCs after weaning using a tamoxifen-inducible Cre expressed under the control of an Ndrg1 promoter. Despite profound deletion of AT1a receptor or ACE in PTCs, the absence of either protein did not influence development of atherosclerosis in either sex. Conversely, mice expressing human angiotensinogen and renin in PTCs or expressing human angiotensinogen in liver but human renin in PTCs did not change atherosclerotic lesion size in male mice.ConclusionWhole-body AT1R inhibition reduced atherosclerosis equivalently in both male and female mice; however, PTC-specific manipulation of the RAS components had no effects on hypercholesterolemia-induced atherosclerosis.